Teaching Management of Islamic Religion Education Based on Virtual Reality at Junior High School - Sudiro Sudiro; Munjin Munjin (STAI Hubbulwathan Duri, 2024)
The rapid advancement of technology has permeated various sectors, including education, introducing innovative tools such as Virtual Reality (VR). VR provides computer-generated simulations that enable immersive interactions between students and teachers within artificial environments. Despite its potential to enhance knowledge and skills, VR adoption in education, particularly in Islamic Religious Education (IRE), remains limited due to challenges such as infrastructure, human resources, and funding. This study investigates the management of VR-based IRE teaching using a qualitative approach. Data were collected through interviews, observations, and document analysis. The data were then processed through reduction, display, and conclusion drawing to provide comprehensive insights into teaching practices and the integration of VR. The findings reveal that IRE teaching management using VR involves three key stages: preparation, action, and evaluation. The use of VR facilitates more effective instructional delivery, engaging students in high-order thinking to solve problems. Furthermore, VR-supported teaching fosters active student participation, increasing engagement by over 35%. The immersive nature of VR creates an interactive and stimulating learning environment, which is particularly beneficial for conveying complex IRE concepts. The integration of VR in IRE presents a promising approach to modernizing religious education and enhancing cognitive and problem-solving skills. However, the study underscores the need to address infrastructural and resource barriers to expand VR adoption in educational settings. This study highlights the potential of VR to revolutionize Islamic Religious Education, emphasizing its role in fostering engagement and higher-order thinking. Efforts to overcome implementation barriers are essential for broader application in education.